PERDAGANGAN PEREMPUAN ANTARNEGARA Perdagangan Amoi di Kota Singkawang, Kalimantan Barat - Agus Sikwan (Populasi, 2006)
Cross country trafficking in women has happened for so many years in many provinces in Indonesia which territory were near other country's territory. This cross country trafficking has become more complex and related to not just inner state territory, but also out side the country. Its pattern was also changed, not just organized by one person, but by a syndicated camouflazed in beauty salons, hotels, and tour travel agents. Its purpose moved from prostitution to become migrant workers and the bride for foreign men. The victims also suffered from many harrasement, physically, psychologically, social and economics. Recruitment agents, customers, husbands/ family, the owners of the place they worked in were the people who caused the harrasement towards them.